Cultivating Foundations: A Research-Driven Community Service for Enhancing Early-Grade Education at SD Negeri OKAS - Riasman; Ester Julinda Simarmata; Rosdiana Samosir (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This abstract highlights the major features and outcomes of the calistung training community service effort done at SD Negeri OKAS. The community service, done on January 10, 2024, aims to increase the core skills of early-grade pupils in reading, writing, and counting through a research-driven, holistic approach. The process involves a detailed needs assessment, collaborative curriculum design, and interactive, culturally sensitive teaching methods. The good and beneficial effects include a noticeable improvement in students' skills, strengthened community bonds, overwhelming favorable comments, heightened awareness of educational relevance, and the formation of lasting collaborations. The endurance of the effort is shown through continued support, mentorship programs, and its significance as a model for similar ventures. As a researcher committed to community service, the success of this effort illustrates the transformative potential of combining research, community participation, and sustainable planning in educational interventions. The reported experiences and outcomes serve as useful tools for shaping future initiatives and add to the greater conversation on effective community-driven educational interventions.